The church and poverty alleviation: The challenges of Congo Evangelistic Mission - Kakwata, Frederick (Missionalia, 2020)
This study utilised the qualitative methodology in which individual data were collected through in-depth semi-structured interviews to investigate the challenges facing the Congo Evangelistic Mission (CEM) in its attempts to alleviate poverty in the city of Lubumbashi. The findings of this study revealed that the CEM’s ability to respond to poverty problems in Lubumbashi holistically is hampered for the most part by individualistic, structural and fatalistic perspectives that underly perceptions of the causes of poverty that shaped the mind of the people. Consequently, the CEM’s intervention in alleviating poverty was found to be insignificant as it was limited to sporadic instances of assistance for the needy. For the CEM to play an active and vital role in tackling poverty, it needs to re-evaluate the theology of missions by expressing the concern for the poor and working towards life transformation.